The Power of Sunspots: An Experimental Analysis - Frank Heinemann; Aniol Llorente-Saguer; Dietmar Fehr (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We present an experiment in which extrinsic signals may generate sunspot equilibria. The game has a unique symmetric non-sunspot equilibrium, which is also risk dominant. Other equilibria can be ordered according to risk dominance. By comparing treatments with different information structure, we measure the force of extrinsic signals. Results indicate that Sunspot equilibria emerge naturally, if there are salient (but extrinsic) public signals. However, salient private signals of high precision may also cause sunspot-like behavior even though this is no equilibrium. The higher the precision of signals and the easier they can be aggregated, the more powerful they are in dragging behavior away from the risk dominant to risk dominated strategies.
Keywords: C72; C92; D84; 330; coordination games; strategic uncertainty; sunspot equilibria; irrelevant information